DOI: 10.26868/25222708.2019.210677
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Orientation, Window Size, and Lighting Control to Climate-Based Daylight Performance and Lighting Energy Demand on Buildings in Tropical Area

Abstract: The use of daylight offers a positive contribution to building energy savings yet also provoke a shortfall anticipation such as the large amount of light and visual discomfort. Moreover, building energy demand will also depend on the lighting control system combined with occupants' behaviour of which is still rarely studied. This paper addressed the evaluation of climate-based daylight performance in a simulated reference office with a single unglazed opening measuring various window-to-wall ratio on one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…O projeto de aberturas é parte integrante de um processo que considera múltiplos aspectos simultaneamente (OCHOA et al, 2012), dentre os principais parâmetros de influência no desempenho luminoso, destaca-se o tamanho da abertura, a orientação, o sombreamento externo e a obstrução do céu visível, conforme apontado em estudos nacionais e internacionais BITTENCOURT;CARAM, 2013;FELIPPE et al, 2015;FONSECA, 2015;CARAM, 2015;CINTRA;AMORIM, 2012). O tamanho da abertura é representado pelo percentual de abertura da fachada (PAF) e tem impacto direto na quantidade de luz (FELA et al, 2019) e no calor que entra no ambiente (TZEMPELIKOS, 2005;FONSECA, 2015). O sombreamento externo é a principal estratégia para evitar os ganhos térmicos e o ofuscamento causado pela luz direta (STACK;GOULDING;LEWIS, 2000;INKAROJRIT, 2005;TZEMPELIKOS, 2005;GALASIU;VEITCH, 2006b;KIM, 2009;KIRIMTAT et al, 2016).…”
Section: Referencial Teóricounclassified
“…O projeto de aberturas é parte integrante de um processo que considera múltiplos aspectos simultaneamente (OCHOA et al, 2012), dentre os principais parâmetros de influência no desempenho luminoso, destaca-se o tamanho da abertura, a orientação, o sombreamento externo e a obstrução do céu visível, conforme apontado em estudos nacionais e internacionais BITTENCOURT;CARAM, 2013;FELIPPE et al, 2015;FONSECA, 2015;CARAM, 2015;CINTRA;AMORIM, 2012). O tamanho da abertura é representado pelo percentual de abertura da fachada (PAF) e tem impacto direto na quantidade de luz (FELA et al, 2019) e no calor que entra no ambiente (TZEMPELIKOS, 2005;FONSECA, 2015). O sombreamento externo é a principal estratégia para evitar os ganhos térmicos e o ofuscamento causado pela luz direta (STACK;GOULDING;LEWIS, 2000;INKAROJRIT, 2005;TZEMPELIKOS, 2005;GALASIU;VEITCH, 2006b;KIM, 2009;KIRIMTAT et al, 2016).…”
Section: Referencial Teóricounclassified
“…As for the North and South orientations, the illuminance values are relatively stable in the entire day, because these orientations are not directly affected by the sun's movement. Moreover, since Bandung is located in the southern hemisphere, the daylight illuminance at the North orientation shall be greater than that at the South [21]. However, the North orientation receives relatively lower daylight illuminance during the measurement because of the little sunlight available throughout the day.…”
Section: Figure 3 Illuminance Values From the Mirror Box Artificial S...mentioning
confidence: 99%
“…A study conducted in New York, Chicago, and Los Angeles has found that the daylight autonomy is highest when the façade is facing south and with the increase of window size, UDI ratio shows similar trend for all orientation except south, as south window receives more daylight compared other orientation, so when the window size increases, the average illuminance on the work plane may increase to more than 1000 lux and thus decreases the UDI ratio (Shen & Tzempelikos, 2010). A study conducted in Indonesia concluded that the south facing openings provides minimum useful daylight illuminance (UDI) and south and west oriented openings with 50% window wall ratio is recommended in tropical region (Fela, Utami, Mangkuto, & Suroso, 2019). Daylight Glare Probability (DGP) is lower at south and west orientation compared to north and east for tropical humid areas (Fela, Utami, Mangkuto, & Suroso, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted in Indonesia concluded that the south facing openings provides minimum useful daylight illuminance (UDI) and south and west oriented openings with 50% window wall ratio is recommended in tropical region (Fela, Utami, Mangkuto, & Suroso, 2019). Daylight Glare Probability (DGP) is lower at south and west orientation compared to north and east for tropical humid areas (Fela, Utami, Mangkuto, & Suroso, 2019). Orientation does not play a relevant role in a space with high window-wall-ratio and bilateral daylighting but the geometric characteristics, built-up surroundings, most influence the daylighting conditions ( Munoz, Esquivias, Moreno, Acosta, & Navarro, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation